MANAGEMENT CONTROL SYSTEMS AND FIRM SUSTAINABILITY: EVIDENCE FROM TEXTILE AND APPAREL BUSINESSES IN THAILAND - Phaprukbaramee Ussahawanitchakit (Asian Academy of Management Journal, 2017)
The objective of this study is to examine the effects of management control systems on the firm sustainability of textile and apparel businesses in Thailand. Management control systems are the main variable of the study, while organisational renewal, management development, business excellence, and firm sustainability are the outcome variables of the study. In this study, 186 textile and apparel businesses in Thailand compose the study sample. A mail survey questionnaire was used for data collection. Additionally, structural equation modelling is utilised to test the research relationships. The results show that management control systems positively impact organisational renewal and firm sustainability. In addition, organisational renewal positively affects management development, business excellence, and firm sustainability. Both management development and business excellence positively influence firm sustainability. However, it is found that management control systems are not related to management development and business excellence. In summary, management control systems can help firms survive and sustain themselves in highly variable environments. To gain a sustainable competitive advantage, superior performance, and long-term sustainability, firms’ executives can pay attention to the development, utilisation, maintenance, and improvement of management control systems. To verify and expand the current study, future research needs to collect data from different populations or larger populations and employ other statistical techniques, such as regression analysis, partial least squares, and path analysis to prove the generalisability of the study.